Using PIT‐tags and portable antennas for quantification of fish movement and survival in streams under different environmental conditions. Issue 2 (23rd April 2021) - Saboret, Grégoire; Dermond, Philip; Brodersen, Jakob
Abstract: While PIT‐tag tracking using mobile antennas is being increasingly used to study fish movement and survival in streams, little is known about the limitations of the method, especially over longer periods of time and under different environmental settings. We used 6 years of data combining tagging, mobile antenna tracking and recaptures of Salmo trutta in multiple small streams in the Lake Lucerne drainage area in Switzerland to evaluate the relative importance of different environmental and intrinsic factors affecting the efficiency of the method. Our study system and experimental design allowed us to accurately verify the continuous presence and survival of recaptured fish in the stream after tracking, which meant that we could estimate detection probability with high confidence. The mean detection probability of tagged trout was 43%, but we found that fish length had a strong negative effect on detection probability, especially in males. Multivariate axes of stream environmental features did not predict efficiency but stream width alone was significantly positively correlated with efficiency. Additionally, stream temperature when tracking had a positive effect on fish detectability. Tag loss at recapture was globally rare (<8%) but common in large postspawn females (>30%). Based on the escape response of fish after detection, we could estimate the proportion of ghost tags, which reached a plateau of around 80% 2 years after tagging. We finally showed that our models of tag loss, fish detection and escape response are needed to interpret detection events. Our results highlight that individual variation in detection probability and tag loss is high and has to be considered for analysis.